Radiofrequency-Based Chondroplasty Creates a Precise Area of Targeted Chondrocyte Death With Minimal Necrosis Outside the Target Zone: A Systematic Review - Garrett R. Jackson, M.D; Luis M. Salazar, M.D; Johnathon R. McCormick, M.D; Varun Gopinatth, B.S; Alex Hodakowski, B.S; Colton C. Mowers, B.S; Suhas Dasari, M.D; Luc M. Fortier, M.D; Daniel J. Kaplan, M.D; Zeeshan A. Khan, B.A; Enzo S. Mameri, M.D; Derrick M. Knapik, M.D; et al. (Elsevier, 2023)
Purpose: To systematically examine the effects of radiofrequency (RF) ablation or coblation (controlled ablation) on chondrocyte viability following knee chondroplasty in preclinical literature to determine the effectiveness and safety of RF-based techniques. Methods: A literature search was performed in September 2022 using PubMed and Scopus using the following search terms combined with Boolean operators: "chondroplasty," "radiofrequency," "thermal," "knee," "chondral defect," "articular cartilage," and "cartilage." The inclusion criteria consisted of preclinical studies examining the effect of RF ablation or coblation on chondrocytes during knee chondroplasty. Exclusion criteria consisted of studies reporting chondroplasty in joints other than the knee, clinical studies, in vitro studies using animal models, case reports, non-full-text articles, letters to editors, surveys, review articles, and abstracts. The following data were extracted from the included articles: author, year of publication, chondral defect location within the knee and chondral characteristics, RF probe characteristics, cartilage macroscopic description, microscopic chondrocyte description, and extracellular matrix characteristics. Results: A total of 17 articles, consisting of 811 cartilage specimens, were identified. The mean specimen age was 63.4 ± 6.0 (range, 37-89) years. Five studies used monopolar RF devices, 7 studies used bipolar RF devices, whereas 4 studies used both monopolar and bipolar RF devices. Time until cell death during ablation at any power was reported in 5 studies (n = 351 specimens), with a mean time to cell death of 54.4 seconds (mean range, 23.1-64) for bipolar RF and 56.3 seconds (mean range, 12.5-64) for monopolar RF devices. Chondrocyte cell death increased with increased wattage, while treatment time was positively correlated with deeper cell death. Conclusions: In this systematic review, histologic analysis demonstrated that RF-based chondroplasty creates a precise area of targeted chondrocyte death, with minimal evidence of necrosis outside the target zone. Caution must be exercised when performing RF-based chondroplasty due to the risk of cell death with increased application time and wattage. Clinical Relevance: Although RF ablation has demonstrated favorable results in preliminary trials, including smoother cartilage and less damage to the surrounding healthy tissue, the risks versus benefits of the procedure are largely unknown. Caution must be exercised when performing RF-based chondroplasty in the clinical setting due to the risk of cell death with increased application time and wattage.